Comprehensive Physiology 2018
DOI: 10.1002/cphy.c180028
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Maps of Transcription Regulatory Elements and Transcription Enhancers in Development and Disease

Abstract: Gene expression is regulated by numerous elements including enhancers, insulators, transcription factors, and architectural proteins. Regions of DNA distal to the transcriptional start site, called enhancers, play a central role in the temporal and tissue-specific regulation of gene expression through RNA polymerase II. The identification of enhancers and other cis regulatory elements has largely been possible due to advances in next generation sequencing technologies. Enhancers regulate gene expression throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 125 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…The advent of chromosome capture technologies has allowed the identification of more interactions between chromosomal regions than ever before (reviewed by Agrawal et al 15 ). A new field emerged through the rise of these techniques: nuclear architecture, the 3-dimensional organization of chromatin within nuclear space ( Fig.…”
Section: The Cohesin Complexmentioning
confidence: 99%
“…The advent of chromosome capture technologies has allowed the identification of more interactions between chromosomal regions than ever before (reviewed by Agrawal et al 15 ). A new field emerged through the rise of these techniques: nuclear architecture, the 3-dimensional organization of chromatin within nuclear space ( Fig.…”
Section: The Cohesin Complexmentioning
confidence: 99%
“…The RegSNP program also suggested that the ECR1(T) allele would bind the CTCF transcription factor with higher affinity. This is intriguing as CTCF is a known marker for the function of regulatory sequences known as insulators that protect promoters against the effects of enhancer sequences (Agrawal, Heimbruch, & Rao, ).…”
Section: Resultsmentioning
confidence: 99%
“…Enhancers are CREs that contain DNA-binding motifs for transcription factors (TFs) distal to the gene promoter, which are located immediately adjacent to the transcriptional start site (TSS). Binding of these TFs drives enhancers to promote or repress gene expression through multiple mechanisms that are beyond the scope of this review ( Li et al, 2016 ; Chen et al, 2018 ; Agrawal et al, 2019 ). Next-generation sequencing-based (NGS) methods have revolutionized the genome-wide identification of enhancers.…”
Section: Enhancersmentioning
confidence: 99%
“…For further information on enhancer and CTCF functions, we suggest these reviews (Ong and Corces, 2014;Shlyueva et al, 2014;Li et al, 2016;Chen et al, 2018;Rowley and Corces, 2018;Agrawal et al, 2019;Braccioli and De Wit, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation